Sintering of a UO2-PuO2 freeze-granulated powder under reducing conditions. Issue 15 (December 2020) - Simeon, Julie; Lebreton, Florent; Ramond, Laure; La Lumia, Florian; Clavier, N.; Bernard-Granger, Guillaume
Highlights: Sintering of MOX fuel under reducing conditions. Densification controlled by grain boundary diffusion and grain growth by the grain boundaries. Activation energy value around 525 kJ/mol was obtained for densification. Homogeneous plutonium and uranium cations spatial distribution. Abstract: A freeze-granulated powder made of UO2 and PuO2, containing 15 mol% of Pu/(U + Pu), was sintered under reducing conditions (oxygen potential of −468 kJ/mol at 1700 °C). Constructing the "grain size versus relative density" trajectory, using the constant rates of heating and the master sintering curves approaches and calculating the diffusion coefficients by exploiting the results of the sintering runs enabled to propose that densification was probably controlled by grain boundary diffusion and grain growth by the grain boundaries. An activation energy around 525 kJ/mol was obtained for densification, which was close to what was reported for grain boundary diffusion of plutonium cations in U0.55 Pu0 .45 O2-x polycrystalline materials. The sintered microstructure appeared homogeneous regarding the plutonium and uranium cations spatial distribution. By combining the master sintering curve approach for anisothermal and isothermal conditions, it was possible to predict the evolution of the relative density over time for any type of thermal path.